The Brain full of holes - Chatterton, Martin (Atlanta [Ga.] : Peachtree, 2010)
Having moved to Switzerland, thirteen-year-old Sheldon and his new stepbrother Theo ("The Brain") Brain investigate a mystery involving particle physics, Swiss cheese, a missing truck driver, and a carnivorous cuckoo clock.
A Junior Library Guild selection
Keywords: Physics -- Juvenile fiction; Stepfamilies -- Juvenile fiction; Switzerland -- Juvenile fiction; Mystery and detective stories; Physics -- Fiction; Stepfamilies -- Fiction; Switzerland -- Fiction; Humorous stories